The Development of Computational Thinking Skills Science E-Worksheets for PGMI Students at PTKIN - Like Raskova Octaberlina; Nur Hidayah Hanifah; Dian Eka Aprilia Fitria Ningrum; Ima Yustianingsih (CV. Creative Tugu Pena, 2026)
Science teachers are involved in the formation of quality human resources. As the times develop, technology is developing rapidly and computational thinking skills are also needed. The purpose of this study is to develop Computational Thinking Skills-based E-Worksheets for PGMI students. The research method uses ADDIE development which consists of five stages of Analyze, Design, Develop, Implement, Evaluate. The subjects of the study are PGMI students in 3 PTKIN, namely UIN Maulana Malik Ibrahim Malang, UIN Kudus, and UIN Mataram. Data collection techniques with observation, interviews, tests, and questionnaires. The data analysis technique uses the independent sample t-test to compare the improvement of student learning outcomes and the Anova Test to compare the differences between PTKIN. The results of the study showed that the learning outcomes in each PTKIN have increased, as shown by the value of sig. all three are 0.000 < 0.05. Meanwhile, the results of the Anova test value sig. 0.042 < 0.05. So it can be concluded that the use of E-woksheets media science computational thinking in improving student learning outcomes, especially in science literacy.